Pancreaticopleural fistula: a case report - Thapa, Bikas; Subedi, Nirajan; Bhandari, Ramesh S. (Journal of Chitwan Medical College, 2018)
Pancreaticopleural fistula is a diagnostic challenge to physicians. The diagnosis should be suspected if a patient presents with pleural effusion in a setting of chronic pancreatitis. The significantly raised amylase in the pleural fluid offers an important clue to the diagnosis. Computed Tomography (CT), Endoscopic retrograde cholangiopancreatography (ERCP) and Magnetic resonance cholangiopancreatography (MRCP) can reveal the fistulous tract between the pancreas and the pleural space. The therapeutic options include medical, endoscopic, as well as surgical interventions. Here we report a case of pancreaticopleural fistula in a chronic alcoholic that was treated successfully by medical management.